2014
DOI: 10.1002/chem.201402765
|View full text |Cite
|
Sign up to set email alerts
|

Modular Synthesis of Phenanthro[9,10‐c]thiophenes by a Sequence of CH Activation, Suzuki Cross‐Coupling and Photocyclization Reactions

Abstract: A total number of 15 different 3,4-diarylthiophenes were synthesized, which bear a chlorine atom in ortho-position of one of the aryl substituents. One aryl group was introduced by an oxidative cross-coupling reaction, involving a CH activation at C4(3) of the thiophene core. The other aryl group was in most cases introduced by a Suzuki cross-coupling reaction, which succeeded the oxidative cross-coupling step. Photocyclization reactions of the 3,4-diarylthiophenes were performed in a solvent mixture of benze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…Bach et al reported in 2011 that thiophenes substituted at C3 by CH 2 PO(OEt) 2 or CH 2 COOEt undergo a regioselective oxidative coupling reaction at C4 with aryl boronic acids in the presence of Ag 2 O, cesium trifluoroacetate [Cs(tfa)], benzoquinone (BQ), and Pd (tfa) 2 catalyst in trifluoroacetic acid as the solvent (Scheme 2, middle) [28]. They recently extended this procedure to a broad range of substrates [29,30]. Studer and Itami also described a procedure for the β-arylations of thiophenes with arylboronic acids under Pd/TEMPO catalysis (Scheme 2, bottom) [31].…”
Section: Arylboronic Acids or Aryl Trifluoroboratesmentioning
confidence: 94%
“…Bach et al reported in 2011 that thiophenes substituted at C3 by CH 2 PO(OEt) 2 or CH 2 COOEt undergo a regioselective oxidative coupling reaction at C4 with aryl boronic acids in the presence of Ag 2 O, cesium trifluoroacetate [Cs(tfa)], benzoquinone (BQ), and Pd (tfa) 2 catalyst in trifluoroacetic acid as the solvent (Scheme 2, middle) [28]. They recently extended this procedure to a broad range of substrates [29,30]. Studer and Itami also described a procedure for the β-arylations of thiophenes with arylboronic acids under Pd/TEMPO catalysis (Scheme 2, bottom) [31].…”
Section: Arylboronic Acids or Aryl Trifluoroboratesmentioning
confidence: 94%
“…The most straightforward approach to the phenanthrothiophenes is by oxidative cyclization of diaryl thiophenes ( 2 , Scheme ); this route also benefits from the synthetic accessibility of diaryl thiophenes with a variety of substituents . However, Schnapperelle and Bach attempted the cyclo‐oxidation of compound 2 under a wide variety of conditions, and found no reaction . To overcome this problem, they prepared the more complicated desymmetrized chlorodiarylthiophene 3 and successfully converted it to phenanthrothiophene 1 by irradiation with 254‐nm light.…”
Section: Figurementioning
confidence: 99%
“…Diaryl thiophene derivatives can be synthesized by a variety of methods . Dang and Chen reported the efficient synthesis of diaryl thiophenes in three steps from the bromoacetophenone ( 4 ) .…”
Section: Figurementioning
confidence: 99%
“…Apart from synthetic applications of this method to the synthesis of new materials,8 we have also investigated the mechanistic course of the reactions. Preliminary results had indicated that an electrophilic palladium species could be the reactive intermediate, which attacked position C5 prior to CC bond formation at C4 5.…”
Section: Introductionmentioning
confidence: 99%